Pengaruh Terapi Tepid Water Sponge Terhadap Penurunan Suhu Tubuh pada Anak Pra Sekolah dengan Demam Thypoid Diruangan Anak RSUD kota Manado - Nelfa Takahepis; Sri Wahyuni; Minar Hutahuruk (Universitas Muhammadiyah Manado, 2024)
Tepid water sponge is a combined therapy of warm compresses and block compresses on superficial blood vessels using a wiping technique which works by widening peripheral blood vessels throughout the body so that heat evaporation from the skin to the surrounding environment is faster. The aim of this study was to determine the effect of tepid water sponge therapy on reducing body temperature in pre-school children with typhoid fever in the children's room at RSUD Kota Manado.This research uses experimental research with a One Group Pre- test Post-test approach. The population is all pediatric patients treated at RSUD Kota Manado. Samples were taken using a purposive sampling technique with stipulations on inclusion criteria. Data collection is done using SOP (Standard Operating Procedure) and observation. Next, the data that has been collected is processed using a computer with a data processing application and analyzed using the T statistical test with a significance level (α) of 0.05. The results of this research show that the resulting value is smaller = 0.000 from the alpha value <0.05. It can be concluded that there is an effect of tepid water sponge therapy on reducing body temperature in children with typhoid fever in the room. This research suggestion can be useful and can add information to lowering the body temperature of pre-school children due to typhoid fever by carrying out tepid water sponge therapy.